Acute capsaicin supplementation improves resistance training performance in trained men - de Freitas, Marcelo Conrado [UNESP]; Cholewa, Jason M.; Freire, Renan V.; Carmo, Bruna A.; Bottan, Jefferson; Bratfich, Murilo; della Bandeira, Murilo P.; Gonçalves, Daniela C.; Caperuto, Erico C.; Lira, Fabio S. [UNESP]; Rossi, Fabrício E. (My University, 2018)
The purpose of this study was to investigate the acute effect of capsaicin supplementation on performance, rate of perceived exertion (RPE), and blood lactate concentrations during resistance exercise in healthy trained young men. Ten resistance-trained men (age = 22.7 ± 4.0 years, mass = 82.3 ± 9.6 kg, and height = 175 ± 0.1 cm) completed 2 randomized, double-blind trials: capsaicin condition (12 mg) or a placebo condition. Forty-five minutes after supplement consumption, subjects performed 4 sets until movement failure in the squat exercise at 70% of 1 repetition maximum with 90 seconds of rest interval between sets. The total mass lifted (total repetitions 3 mass lifted) was calculated. The RPE was recorded after the last set. Blood lactate was analyzed after each set of exercise, immediately postexercise, and after 3, 5, and at 30 minutes during recovery. The number of repetitions in each set decreased significantly after all sets compared with set-1 and after set-3 and set-4 in relation to set-2 (p < 0.001); however, total mass lifted was higher in capsaicin compared with placebo (3,919.4 ± 1,227.4 kg vs. 3,179.6 ± 942.4 kg, p = 0.002). Blood lactate increased significantly after each set (p < 0.001); however, there were no differences between conditions. Rate of perceived exertion was significantly less for the capsaicin condition than placebo (17.2 ± 1.0 vs. 18.3 ± 1.7, p = 0.048). In summary, acute capsaicin supplementation improves lower-body resistance training performance in trained young men.
Keywords: Ergogenic; Nutrition; Strength exercise